Hubungan Pengetahuan Dengan Kejadian Anemia Pada Remaja Putri Prodi D III STIKes Panca Bhakti Lampung - Akma Listiana; Novi Eniastina Jasa (Universitas Mitra Indonesia, 2022)
AbstractAnemia is a global public health problem, especially in developing countries, which is estimated to occur in 30% of the world's population. According to WHO in 2008 the prevalence of anemia reached 24.8%, while in Indonesia it reached 21.7% and was included in the category of moderate public health problem so that it should receive special attention. Based on the 2004 SKRT, it was stated that the highest prevalence of anemia was found in adolescent girls aged 10-18 years at 57.1%. Riskesdas 2013 data shows that nationally, the proportion of anemia in adolescent girls aged 15-24 years is 18.4%. In May 2022, a presurvey for measuring hemoglobin levels using the Sahli method was conducted and knowledge measurement using a questionnaire was carried out on 10 level 1 female students of the DIII Midwifery Study Program and it was found that 7 people had anemia and lacked knowledge about anemia. The research design is correlational descriptive with a cross sectional approach. The number of samples is 26 students of 1st semester 2 Midwifery DIII Study Program. The sampling technique is total sampling using univariate and bivariate analysis. The results of the study obtained Knowledge of Young Women with the incidence of anemia in the DIII Midwifery Study Program of STIKes Panca Bhakti Lampung in June 2022, namely good knowledge of 20 people or 76.9%, poor knowledge of 6 people or 23.1%% and there is a relationship between knowledge and the incidence of anemia with a chi square value of 0.028. The conclusion of the study is that there is a significant relationship between the knowledge of young women and the incidence of anemia. From these conclusions, the authors provide suggestions for the community, health service institutions, educational institutions and research sites to further increase adolescent knowledge about anemia. Keywords : Knowledge of Young Women, Anemia.